Effect of Altitude and Tilt Angle on Solar Radiation in Tropical Regions - Aldobhani, Abdul-Aziz Mohamed Saeed (University of Science and Technology, Yemen, 2014)
Solar radiation is the main factor that affects the PV system design. Because of high shortage in solar radiation data in many regions, the mathematical models are necessary to use in solar radiation data estimation. In this study Hotel method is modeled and applied to extend the knowledge about the solar radiation on horizontal surface, fixed tilt surface and optimal tilt angle surface in tropical climate regions. In addition, the study inspects in the effect of altitude on solar radiation, and analyzes the variation in solar radiation data in areas that have high diversity in altitude regions. The data provides the PV system designer the exact percentages increase in solar radiation in important times in the year caused by rising in altitude and shifting the tilt angle from horizontal to optimum fixed annually tilt angle and optimum daily tilt angle. The study concludes to the main recommendations that can help the PV system designers to improve the output of PV system. In addition, the study analyzes the combination effect of solar radiation in different altitudes and tilt angles to recommend the designers the procedures of improving the peak sun hours of design month for PV systems.